Key issues in the persistence of poliomyelitis in Nigeria: a case-control study - Dr. Tara D Mangal, PhD; R Bruce Aylward, MD; Michael Mwanza, BComm; Alex Gasasira, MBChB; Emmanuel Abanida, MBChB; Prof. Muhammed A Pate, MD; Prof. Nicholas C Grassly, PhD (Elsevier, 2014)
Background: The completion of poliomyelitis eradication is a global emergency for public health. In 2012, more than 50% of the world's cases occurred in Nigeria following an unanticipated surge in incidence. We aimed to quantitatively analyse the key factors sustaining transmission of poliomyelitis in Nigeria and to calculate clinical efficacy estimates for the oral poliovirus vaccines (OPV) currently in use. Methods: We used acute flaccid paralysis (AFP) surveillance data from Nigeria collected between January, 2001, and December, 2012, to estimate the clinical efficacies of all four OPVs in use and combined this with vaccination coverage to estimate the effect of the introduction of monovalent and bivalent OPV on vaccine-induced serotype-specific population immunity. Vaccine efficacy was determined using a case-control study with CIs based on bootstrap resampling. Vaccine efficacy was also estimated separately for north and south Nigeria, by age of the children, and by year. Detailed 60-day follow-up data were collected from children with confirmed poliomyelitis and were used to assess correlates of vaccine status. We also quantitatively assessed the epidemiology of poliomyelitis and programme performance and considered the reasons for the high vaccine refusal rate along with risk factors for a given local government area reporting a case. Findings: Against serotype 1, both monovalent OPV (median 32·1%, 95% CI 26·1-38·1) and bivalent OPV (29·5%, 20·1-38·4) had higher clinical efficacy than trivalent OPV (19·4%, 16·1-22·8). Corresponding data for serotype 3 were 43·2% (23·1-61·1) and 23·8% (5·3-44·9) compared with 18·0% (14·1-22·1). Combined with increases in coverage, this factor has boosted population immunity in children younger than age 36 months to a record high (64-69% against serotypes 1 and 3). Vaccine efficacy in northern states was estimated to be significantly lower than in southern states (p≤0·05). The proportion of cases refusing vaccination decreased from 37-72% in 2008 to 21-51% in 2012 for routine and supplementary immunisation, and most caregivers cited ignorance of either vaccine importance or availability as the main reason for missing routine vaccinations (32·1% and 29·6% of cases, respectively). Multiple regression analyses highlighted associations between the age of the mother, availability of OPV at health facilities, and the primary source of health information and the probability of receiving OPV (all p<0·05). Interpretation: Although high refusal rates, low OPV campaign awareness, and heterogeneous population immunity continued to support poliomyelitis transmission in Nigeria at the end of 2012, overall population immunity had improved due to new OPV formulations and improvements in programme delivery. Funding: Bill & Melinda Gates Foundation Vaccine Modeling Initiative, Royal Society.